How Ciliated Protists Survive by Cysts: Some Key Points During Encystment and Excystment - Li, Yuqing; Wang, Yurui; Zhang, Shijing; Maurer-Alcalá, Xyrus X.; Yan, Ying (Frontiers in Microbiology, 2022)
Forming cysts is a common and important bionomic strategy for microorganisms to persist in harsh environments. In ciliated protists, many species have been reported to form cysts when facing unfavorable conditions. Despite traditional studies on the morphological features of cysts and the chemical composition of cyst wall, recent research has focused more on the molecular mechanisms of encystment. The present work reviews studies on developmental features and molecular information of resting cysts in ciliates, and pays more attention to the following questions: what are the inducing factors of encystment and excystment? How does the cell change morphologically during these dynamic processes? And what molecular mechanisms underlie those changes? We also present and summarize the characteristics of cysts from diverse ciliate lineages in a phylogenetic framework, aiming to provide new perspectives for studies on adaptive evolution of unicellular eukaryotes.